Anti-Inflammatory Activity of Hydroxytriazenes and their Vanadium Complexes - Kalpana Singh; Peeyush Patel; A. K. Goswami (E-Journal of Chemistry)
The anti-inflammatory activity of hydroxytriazenes as well as their vanadium complexes has been studied using carrageenan induced hind paw oedema method in albino rats (Wister strain). Hydroxytriazenes viz., 3-hydroxy-1,3-diphenyltriazene (HT-1), 3-hydroxy-3-phenyl-1-(4-sulfonamido)phenyl triazene (HT-2), 3-hydroxy-3-p-chlorophenyl-1-(4-sulfonamido) phenyltriazene (HT-3), 3-hydroxy-3-m-chlorophenyl-1-(4-sulfonamido)phenyltriazene (HT-4)(HT-4) and their respective vanadium complexes C-1, C-2, C-3 and C-4 have been synthesized using standard methods, purified, characterized and used for studying their anti-inflammatory activities. The hind paw oedema was produced by subplanter injection of carrageenan and the paw volume was measured plethysmographically after 0.5, 1, 2, 3 and 5 h. The animals were given HT-1, HT-2, HT-3 and HT-4 and also vanadium complexes C-1, C-2, C-3 and C-4 dissolved in DMSO (at dose 5 mg/Kg body weight). Diclofenac sodium (5 mg/kg) was used as a standard drug. The standard drug shows maximum inibition up to 1h as 81.73% which goes on increasing up to 3h (88.94%) but further reduces to 74.93% at the end of 5 h. The test compounds i.e. both ligands as well as their metal complexes show maximum percent inhibition only up to 1h. after which the efficacy reduces. Thus it can be said that both ligands as well as their vanadium complexes show very significant anti-inflammatory activity up to 1h which is comparable to standard drug.